Uso conjunto do EPANET e da metodologia de Morgan para otimização de redes de abastecimento de água - Costa, Luis Henrique Magalhães (2005)
A large number of researches have been carried out in the area of optimization of water supply systems, mainly due to the saving that the optimal design provides. Water distribution systems constitute relevant importance in the great sectors of the society, because they supply consumption points such as residences, industries, stores and hospitals. The execution of this work aims at studying about the optimization methodology in systems of water distribution presented by Morgan & Goulter (1985). Such method happens in two stages: the procedure of hydraulic balance, seeking to guarantee the hydraulic consistence and the adjustments of the diameters through the linear programming, aiming at a smaller cost. EPANET was the chosen program for the calculation of the hydraulic balance of the net, due to its wide acceptance, and for making possible the communication with computational routines created for specific applications. However, it was developed a program denominated UFC4 presenting an interface in language DELPHI that will serve as mediator among the software EPANET and the routine of the linear programming elaborated in language FORTRAN. The studies were applied in three examples of real meshed nets, having as comparison parameter other optimization methodologies. The accomplished analysis consider only the distribution system, having the reservoir a fixed and predetermined piezometric level. The results obtained with the program have shown economical advantages when compared to other optimization methodologies, thus confirming the efficiency of the methodology used in this work.